THE ESSENCE OF THE STAGES OF FORMING THE INFORMATION COMPETENCE OF THE TRANSLATOR - Svitlana M. Amelina; Rostyslav O. Tarasenko (Інформаційні технології і засоби навчання, 2018)
The paper analyses the formation of informational competence of translators in the Bachelor and Master degree programs. The structure and content of the informational competence of the translator are considered in the context of its coordination with the educational programs of translators and the standards of the translation services. There have been determined the stages of formation of the informational competence of the translators such as constructive, technological and integration, their correlation with the periods of study of the future translators, levels of their mastery of information technologies. The outcomes of each stage are specified and described in detail. It has been stated that one way to achieve high efficiency in the formation of information competence of translators may be the implementation of a comprehensive translation task individually for each student with the prospect of its realization throughout the training period in accordance with certain stages of the formation of information competence. The content and tasks of the stages of the formation of the informational competence of translators are determined. The goals of the stages of the information technologies study are detailed by a complex of information, qualification and scientific achievements: electronic terminology databases of a specialized field in several areas; translation memory bases for use in automated translation systems; the base of electronic links to terminological resources network; the base of electronic references to the corpus of parallel texts; certificates of traineeship in production structures for using automated translation systems or terminological management systems; certificates of knowledge of specialized software in translation from manufacturing companies, their dealers, certification centers.